Hospitalization rates and resource utilization of schizophrenic patients switched from oral antipsychotics to aripiprazole-depot in Germany - Christoph Potempa; Reinhard Rychlik (Health Economics Review, 2018)
Objective: Examine cost-driving factors of schizophrenia in Germany for patients prior- and post-switch from an oral antipsychotic therapy to aripiprazole-depot and perform a budget impact analysis (BIA) referring to the context of German health care. Methods: A single-armed, retrospective, non-interventional pre-post comparison study with 132 patients to compare the total psychiatric hospitalization rates and the associated costs of both, the treatment with oral antipsychotics and aripiprazole-depot. The BIA was performed to compare both treatment periods with respect to health-related costs. A subsequent univariate sensitivity analysis examined the robustness of the results. Results: After switching the treatment to aripiprazole-depot, the total psychiatric hospitalization rates for the 6-month treatment period were significantly (p < 0.001) lower (14%) compared to the hospitalization rates when treated with oral antipsychotics (55.1%). 18.2% of the patients reported to be employed, with 29.2% having work incapacities. The mean number of schizophrenia episodes was 2.58 episodes per patient during the oral-antipsychotic treatment compared to 0.41 episodes per patient during the aripiprazole-depot phase (p < 0.001). The treatment with aripiprazole-depot also significantly reduced the mean number of hospitalizations per patient (0.63 to 0.16, p < 0.001) and the mean number of hospitalized days (27.39 to 5.56, p < 0.001) compared to the oral antipsychotic treatment. Additionally a significant reduction of the mean stay in day-clinics and psychiatric institute ambulances (PIAs) was observed (46.13 days to 7.29 days, p < 0.01). Treatment of a patient suffering from schizophrenia with oral antipsychotics produced costs of 9935.38 exteuro (direct costs: 9498.36 exteuro), while aripiprazole-depot generated costs of 4557.56 exteuro (direct costs: 4449.83 exteuro) per patient for a one-year observation period. This resulted in total costs of 6,517,606,265.43 exteuro for the oral antipsychotic treatment and 2,989,756,603.05 exteuro for aripiprazole-depot treatment from the perspective of the German health care system. The results remained robust during sensitivity analysis, with aripiprazole-depot being the more cost-effective strategy. Conclusions: The results suggest that aripiprazole-depot treatment for schizophrenia patients has major potential in terms of cost savings for the German statutory health insurance.
Keywords: 330; Schizophrenia; Aripiprazole-depot; Long-acting injectable; Hospitalization; Budget-impact-analysis